2016
DOI: 10.1002/pro.2890
|View full text |Cite
|
Sign up to set email alerts
|

G‐LoSA: An efficient computational tool for local structure‐centric biological studies and drug design

Abstract: Molecular recognition by protein mostly occurs in a local region on the protein surface. Thus, an efficient computational method for accurate characterization of protein local structural conservation is necessary to better understand biology and drug design. We present a novel local structure alignment tool, G-LoSA. G-LoSA aligns protein local structures in a sequence order independent way and provides a GA-score, a chemical feature-based and size-independent structure similarity score. Our benchmark validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…G‐LoSA is a computational tool to align protein local structures in a sequence order independent way and to provide a G‐LoSA Alignment score (GA‐score), a size‐independent quantity of structural similarity for a given structure pair . G‐LoSA generates possible structure alignments between two structures by iterative maximum clique search and fragment superposition based on the geometry of Cα atoms (i.e., single‐point representation of each residue).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…G‐LoSA is a computational tool to align protein local structures in a sequence order independent way and to provide a G‐LoSA Alignment score (GA‐score), a size‐independent quantity of structural similarity for a given structure pair . G‐LoSA generates possible structure alignments between two structures by iterative maximum clique search and fragment superposition based on the geometry of Cα atoms (i.e., single‐point representation of each residue).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we have developed an efficient local structure alignment tool, Graph‐based Local Structure Alignment (G‐LoSA; https://compbio.lehigh.edu/GLoSA). A recent comprehensive benchmark performance evaluation study reports that G‐LoSA offers a fairly robust overall performance over other widely used local structure alignment tools . Stalis is developed to design ligands by harnessing structure templates identified by G‐LoSA from the PDB structure libraries of small molecule ligands and their chemical fragments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more complete list of binding-site comparison methods is found in a review by Jalencas and Mestres. [45] There were five methods which were able to successfully accommodate calculations of large datasets, Apoc [38], G-LoSA [46], ProBis [47], FuzCav [48], and PocketMatch [49]. Apoc was chosen due to its efficiency, as it is prohibitive to utilize all four programs on the entire dataset simply to benchmark a best fit.…”
Section: New Features and Functionalitiesmentioning
confidence: 99%
“…Studies have shown that compounds derived from natural products are more active than compounds of other origins. After years of research and development in drug production, researchers have developed a variety of methods for predicting drug-likeness, such as virtual screening methods, pharmacophore model methods, and machine learning algorithms, which are widely used in various types of compounds [ 11 , 12 , 13 , 14 , 15 ]. The prediction of medicinal properties also has a good effect on the prediction of the drug-like properties of Chinese herbal medicine-derived compounds.…”
Section: Introductionmentioning
confidence: 99%